Evaluation of the safety and effectiveness of tubal inflammatory drugs in patients with incomplete tubal obstruction after four-dimensional hysterosalpingo-contrast-sonography examination - Yue Zhang; Qin Wang; Chun-yan Gao; Hong-ju Tian; Wen-jiao He; Xi Zhang; Xi Xiong (BMC, 2022)
Abstract Background To investigate the safety and effectiveness of tubal inflammatory drugs in patients with incomplete tubal obstruction of at least one side after four-dimensional hysterosalpingo-contrast-sonography (4D-HyCoSy) examination. Methods Two hundred fifteen cases of tubal incomplete obstruction were diagnosed by ultrasonography from February 2019 to November 2020.According to retrospective analysis,the patients in this study were divided into experimental and control groups; the experimental group combined with salpingitis drugs, and the control group received blank control. Basic information, degree of pain, postoperative complications, and pregnancy rate were then compared between the two groups. Results Compared with the control group, there was no significant difference in the basic information; in preoperative, intraoperative, or postoperative pain; or in postoperative complications (P > 0.05). The cumulative pregnancy rate of the experimental group (26.8%) was statistically different from that of the control group (14.4%) (P < 0.05). Conclusions We observed that for infertile patients with incomplete obstruction of at least one fallopian tube as diagnosed by contrast-enhanced ultrasonography, salpingitis-treatment drugs effectively improved the pregnancy rate postoperatively, with high effectiveness and safety. This regimen is thus worthy of further investigation and promotion in the future.